Negative Space: Student Voice of Green Space and Joy for Urban Planning in Malang - Amelia, Salsabila Putri; Adawiyah, Siti Robiah; Diyanta, Dessy Kiyrana Putri; Bakhitah, Abidah; Abqoriyah, Rifqi; Salsabila Putri; Siti Robiah; Dessy Kiyrana Putri; Sholikhah, Dewi Mar'atus (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2024)
Public spaces, including green open spaces, play a major role in improving the quality of life of the surrounding community. However, the mismatch between urban planning and actual utilization triggers negative perceptions of such spaces, because it can affect their functionality, aesthetics, and social comfort. Previous studies have documented the benefits of ecology, social, and mental health in humans from green open spaces, but previous observations have paid little attention to the less functional or neglected parts (negative spaces). In addition, students' opinions on green open spaces are less considered. This observation uses a quality method by exploring how students' perspectives and opinions on less functional or neglected green open spaces (negative spaces) and encouraging students towards urban planning. Data collection was carried out through in-depth interviews, participatory observation, and visual documentation in green open spaces frequently visited by students in Malang. Thematic analysis revealed diverse student experiences, with common concerns about neglected areas, lack of maintenance, and suboptimal functions, which reduce feelings of joy and comfort. The results of the study provide an answer that negative space indicates a sense of discomfort and lack of social interaction, and is contrary to the purpose of green open space which can provide restorative benefits. These findings provide valuable advice in planning a more inclusive and functional urban spatial plan in the future, ensuring that green open space is used effectively and improves social cohesion and quality in the midst of the urban environment